Draft Genome Sequences of Two Heat-Resistant Mutant Strains (A52 and B41) of the Photosynthetic Hydrogen-Producing Bacterium Rhodobacter capsulatus - Gokce, Abdulmecit; Cakar, Zeynep Petek; Yucel, Meral; Ozcan, Orhan; Sencan, Sevde; Sertdemir, Ibrahim; Erguner, Bekir; Yuceturk, Betul; Sarac, Aydan; Yuksel, Bayram; Ozturk, Yavuz (American Society for Microbiology, 2016)
ABSTRACT The draft genome sequences of two heat-resistant mutant strains, A52 and B41, derived from Rhodobacter capsulatus DSM 1710, and with different hydrogen production levels, are reported here. These sequences may help understand the molecular basis of heat resistance and hydrogen production in R. capsulatus .
Keywords: Prokaryotes